Method for manufacturing electrode mixture for use in all-solid-state sodium storage battery, and method for manufacturing all-solid-state sodium storage battery using the same

JP7668479B2Active Publication Date: 2025-04-25NATIONAL INSTITUTE OF ADVANCED INDUSTRIAL SCIENCE & TECHNOLOGY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2020166582
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-09-30
Publication Date
2025-04-25
Estimated Expiration
2040-09-30

AI Technical Summary

Technical Problem

Existing all-solid-state sodium storage batteries face challenges in achieving high ionic conductivity and electronic conductivity between the solid electrolyte and active material, leading to limited capacity and cycle performance, with issues such as separation, heterogeneous phases, and structural integrity during firing.

Method used

A method involving coating or supporting a resin-based binder on transition metal polyphosphate particles to form composite particles, followed by pressure application, thermal decomposition to create voids, and immersion in organic electrolytes to enhance conductivity, ensuring both ionic and electronic conductivity.

Benefits of technology

The method results in an electrode mixture with improved charge-discharge cycle characteristics and high discharge capacity at room temperature, maintaining structural integrity and enhancing ion conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000024_0000
    Figure 00000024_0000
  • Figure 00000025_0000
    Figure 00000025_0000
  • Figure 00000025_0001
    Figure 00000025_0001
Patent Text Reader

Abstract

To provide a manufacturing method of an electrode mixture used in an all-solid-state sodium storage battery, which can exhibit excellent charge / discharge cycle characteristics while maintaining a high discharge capacity in a room temperature environment, also provide a manufacturing method of an all-solid-state sodium storage battery, which uses the electrode mixture obtained by the manufacturing method of the electrode mixture as a negative electrode and / or a positive electrode.SOLUTION: A manufacturing method of an electrode mixture includes a step A of forming composite particles by coating or supporting a resin-based binder on the particle surface of a polyphosphate transition metal oxide, a step B of filling the composite particles in a powder molding die and then applying pressure to obtain a pellet, and a step C of thermally decomposing the resin binder contained in the pellet to generate voids by heat treatment, and there is also provided a manufacturing method of an all-solid-state sodium storage battery using the electrode mixture.SELECTED DRAWING: Figure 4
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for manufacturing an electrode composite material used in an all-solid-state sodium battery, and a method for manufacturing an all-solid-state sodium battery using the same.

Background Art

[0002] The fields of use of rechargeable batteries (secondary batteries) having a high energy density have expanded in recent years from power sources for portable devices such as smartphones and tablet terminals to electric vehicles and power storage. In particular, automobile manufacturers are actively promoting the development and commercialization of clean vehicles (such as electric vehicles and plug-in hybrid vehicles) in order to comply with environmental regulations aimed at reducing automobile exhaust gas and carbon dioxide (CO2) globally.

[0003] In addition, in renewable energy such as wind power and solar power, a large-scale power storage system is required because the power generation amount greatly fluctuates due to environmental influences. Recently, the power generation cost by renewable energy has become less than half compared to coal-fired power generation, and the power generation amount share is expanding. In view of future widespread use, an improvement in battery production volume is required.

[0004] Rechargeable batteries are indispensable in energy conservation, the introduction of new energy, or clean vehicles, etc., and are positioned as important key devices from the perspective of the economic growth of each country.

[0005] Current rechargeable batteries such as lithium-ion batteries have driven industries such as the electronics and automotive industries. However, depending on the battery application, deficiencies such as temperature characteristics and ensuring safety have delayed full-scale adoption. Therefore, while achieving both high performance and high safety of the battery, the development of new batteries tailored to the application is desired. Also, for resources with rare metals and uneven distribution of production regions, risk management considering factors such as large fluctuations in market prices and the risk of becoming difficult to obtain is important. Although the development of recycling technologies for rare metals has progressed from various perspectives, the development of batteries composed of materials that are inexpensive, easy to obtain, and do not have uneven production regions is required (Non-Patent Document 1 and Non-Patent Document 2).

[0006] Currently, as a battery system that can solve such problems, the development of sodium-ion batteries, particularly all-solid-state batteries, is progressing.

[0007] Sodium is abundantly contained in seawater and is the sixth most abundant element in the earth's crust. It is inexpensive, easy to obtain, and its production regions are not uneven like those of lithium. Therefore, the risk of resource procurement is reduced, and cost reduction of the battery is expected.

[0008] Although it is a very attractive element in the recent trend of being rare-metal-free, compared to lithium, its redox potential is about 0.3 V higher, its ionic volume is more than twice as large, and its atomic weight is about 3.3 times as large. Simply replacing the ion species of conventional lithium-ion batteries with sodium ions makes it difficult to obtain sufficient capacitance and cycle characteristics.

[0009] In addition, as battery systems using sodium, there are sodium-sulfur batteries and sodium-metal chloride batteries. In sodium-sulfur batteries, sodium-containing aluminum oxide such as β-alumina or β''-alumina is used as a solid electrolyte, sodium is used as a negative electrode active material, and sulfur is used as a positive electrode active material.

[0010] In sodium-metal chloride batteries, the solid electrolyte and negative electrode active material are the same, but metal chlorides such as NaAlCl4, NiCl2, FeCl2, CoCl2, and CrCl2 are used as the positive electrode active material.

[0011] Sodium-sulfur batteries and sodium-metal chloride batteries do not require an electrolyte solvent, but unlike lithium-ion batteries and sodium-ion batteries, they do not operate at room temperature. Therefore, an external heat source is used to maintain the battery temperature at 250-350°C, melting the negative and positive electrode active materials and improving the ionic conductivity of the solid electrolyte.

[0012] On the other hand, an all-solid-state battery is a battery system that uses a solid electrolyte. Because this solid electrolyte is responsible for ion conduction between the positive and negative electrodes, it can be produced without using organic solvents, which were necessary for sodium-ion batteries (sodium storage batteries that use an electrolyte). For example, in sodium-ion batteries, sodium hexafluoride phosphate (NaPF6) salt has been used exclusively as the electrolyte, but in the charging and discharging of the battery, sodium ions (Na + In addition to ), hexafluorophosphate ions (PF6 - Because the ions also move, it was considered difficult to make the sodium ion transport fraction equal to 1.

[0013] However, in inorganic solid electrolytes, concentration polarization does not occur, and the transportity of sodium ions is nearly 1. By selecting an electrolyte with an appropriate potential window, side reactions such as the dissolution of the active material, gas generation due to electrolysis, and precipitation of electrolyte decomposition products can be suppressed. Furthermore, ignition of gases and liquids, and leakage are less likely to occur, which is expected to result in a battery with superior safety and reliability.

[0014] All-solid-state sodium batteries, like conventional batteries, consist of a positive electrode, a negative electrode, and an electrolyte, but the electrolyte must be solid and have sodium ion conductivity.

[0015] The positive and negative electrodes are composed of an active material capable of intercalating or alloying sodium ions during charging and discharging, and a solid electrolyte. For example, known active materials for the positive electrode include TiS2 (e.g., Non-Patent Document 3), NaMO2 (M=Co,Ni,Mn,Fe) (e.g., Non-Patent Documents 4-6), Na2MnO3-NaMO2 (e.g., Patent Document 1), and NaMP2O7 (e.g., Patent Document 2). Known active materials for the negative electrode include hard carbon (e.g., Patent Document 3), soft carbon (e.g., Patent Document 4), elements or compounds of tin or antimony (e.g., Patent Documents 5, 6), and sodium metal.

[0016] Through vigorous research and development to date, various solid electrolytes exhibiting high ionic conductivity have been discovered (for example, Patent Documents 7-10). Many of these are amorphous or crystalline, composed of sodium salts and inorganic derivatives.

[0017] However, these materials are in powder or sheet form, and many of them are highly reactive with water, making it impossible to directly apply conventional battery production methods. Specifically, in all-solid-state sodium batteries, unlike liquid-type sodium-ion batteries, it is difficult to permeate the electrolyte into the active material layer of the electrodes to construct ion conduction pathways. Therefore, it is necessary to incorporate a solid electrolyte into the active material layer to enhance the ion conductivity between the solid electrolyte and the solid particles of the active material.

[0018] For example, Patent Documents 11, 12, and 7 propose an electrode composite material precursor (active material layer precursor) containing an active material precursor powder and a solid electrolyte powder, and then firing this precursor to produce an electrode composite material (active material layer) consisting of an active material and a solid electrolyte, or an all-solid-state sodium battery using the same. For example, Na2FeP2O7 crystallized glass is used as the active material precursor. Glass and crystallized glass crystallize through firing (heat treatment), and this process causes softening and flow. Therefore, it can be integrated with solid electrolyte powder by firing alone, without pressurization.

[0019] Furthermore, according to Patent Documents 11, 12, and Non-Patent Document 7, the electrode material is formed on one surface of the solid electrolyte layer by applying the electrode material precursor to one surface of the solid electrolyte layer and then firing it at 400°C or higher.

[0020] However, since solid electrolytes do not have electronic conductivity, it is difficult to ensure both electronic and ionic conductivity in the electrodes. Adding a conductive additive is an easy solution. However, if the conductive additive content is too high, the amount of active material per unit mass of the electrode composite decreases, which tends to reduce the charge-discharge capacity. Furthermore, inhibiting sintering can disrupt ion conduction paths, suggesting a decrease in charge-discharge capacity and discharge voltage. [Prior art documents] [Patent Documents]

[0021] [Patent Document 1] Japanese Patent Publication No. 2014-229452 [Patent Document 2] Japanese Patent Publication No. 2018-32536 [Patent Document 3] International Publication No. 2010 / 109889 [Patent Document 4] Japanese Patent Publication No. 2013-171798 [Patent Document 5] International Publication No. 2013 / 065787 [Patent Document 6] Japanese Patent Publication No. 2015-28922 [Patent Document 7] Japanese Patent Publication No. 2010-15782 [Patent Document 8] Japanese Patent Publication No. 2017-37769 [Patent Document 9] Japanese Patent Publication No. 2019-57495 [Patent Document 10] Japanese Patent Publication No. 2019-57496 [Patent Document 11] Japanese Patent Publication No. 2018-18578 [Patent Document 12] Japanese Patent Publication No. 2016-42453 [Non-patent literature]

[0022] [Non-Patent Document 1] Takashi Mukai: Automotive Technology, 5(4), 19-24 (2018) [Non-Patent Document 2] Takashi Mukai: "Lithium-ion batteries - Development for performance improvement and trends in the automotive LIB industry," Part 1, Chapter 6, Science & Technology, pp. 91-94 (2019) [Non-Patent Document 3] GH Newman,LPKlemann:J.Electrochem.Soc.127,2097-2099(1980) [Non-Patent Document 4] J.-J. Braconnier, C. Delmas, C. Fouassier, P. Hagenmuller: Mat. Res. Bull., 15, 1797-1804 (1980) [Non-Patent Document 5] S. Okada, Y. Takahashi, T. Kiyabu, T. Doi, J. Yamaki, T. Nishida: ECS Meeting Abstr., 602, 201 (2006) [Non-Patent Document 6] N. Yabuuchi, M. Kajiyama, J. Iwatate, H. Nishikawa, S. Hitomi, R. Okuyama, R. Usui, Y. Yamada, S. Komaba: Nat. Mater., 11, 512-517 (2012) [Non-Patent Document 7] H. Yamauchi, J. Ikejiri, F. Sato, H. Oshita, T. Honma, T. Komatsu: J. Am. Ceram. Soc., 102(11), 6658-6667 (2019) [Overview of the project] [Problems that the invention aims to solve]

[0023] As mentioned above, improving the performance of all-solid-state sodium batteries requires technologies that enhance ionic conductivity between the solid electrolyte and the solid particles of the active material while ensuring the electronic conductivity of the electrodes.

[0024] As described in Patent Documents 11, 12 and 7, the present inventors focused on a technique for integrating an electrode composite precursor (electrode active material layer precursor) consisting of an active material precursor powder and a solid electrolyte powder by press molding or by adding a solvent to form a slurry (paste), and then firing it, thereby integrating the active material and the solid electrolyte.

[0025] To improve the performance of batteries, it is necessary to increase the capacity of the positive electrode formed per unit area on the surface of the solid electrolyte layer, which requires increasing the amount of electrode composite material applied per unit area on the surface of the solid electrolyte layer to increase the amount of electrode active material supported. However, as described in Patent Documents 11 and 12, when a mixture consisting of an active material precursor and a solid electrolyte is thickly applied to the electrolyte surface and fired to increase the amount of supported material, only the electrode composite material layer sinters and shrinks, causing it to detach from the electrolyte and preventing the battery from functioning.

[0026] Furthermore, during firing, heterogeneous crystalline phases may be generated. Since these heterogeneous crystalline phases are reaction products of the active material precursor powder and the solid electrolyte powder, they may form at the interface between the active material and the solid electrolyte. Additionally, by coating one surface of the solid electrolyte layer with this electrode composite precursor and then firing it, it is possible to integrate the solid electrolyte layer and the electrode composite (active material layer). In this case, however, heterogeneous crystalline phases may be present at the interface between the solid electrolyte layer and the electrode composite.

[0027] The inventors' investigations revealed that this heterogeneous crystalline phase does not function as a practical active material, and its ionic conductivity is significantly inferior to that of the solid electrolyte layer, thus contributing to a decrease in battery performance.

[0028] For example, when a mixture consisting of an active material precursor (powder of Na2FePO4 crystallized glass) and a solid electrolyte (powder of β"-alumina) is calcined (at an atmosphere of N2 / H2 mixed gas (=96 / 4 vol.%), at 550°C for 1 hour, at 3°C / min), heterogeneous phases (NaFePO4 and Na7(AlP2O7)PO4) may be formed in the composite layer in addition to the active material (Na2FePO4 crystals) and solid electrolyte (β"-alumina). Although NaFePO4 has a similar composition to LiFePO4, a typical active material, its crystal structure is completely different because the ion sizes of Li and Na are different. Compared to LiFePO4, NaFePO4 has a narrower ion conduction path, resulting in higher resistance and lower discharge capacity. Na7(AlP2O7)PO4 exhibits sodium ion conductivity in high-temperature environments above 300°C, but does not function as a practical solid electrolyte at room temperature.

[0029] Incidentally, in order to increase the capacity of batteries, it is necessary to form the solid electrolyte layer with a larger amount of electrode composite material. The electrodes of typical rechargeable batteries (for example, nickel-metal hydride batteries, lithium-ion batteries, etc.) contain a resin-based binder to bind the powdered active material. However, when glass, crystallized glass, or glass containing crystals is used as the active material precursor and firing is performed at temperatures above 400°C, the resin-based binder decomposes thermally, causing the electrodes to detach. This is particularly pronounced when the active material precursor, which undergoes significant volume shrinkage during firing, is included in the electrode composite material, easily causing the structure of the electrode composite material (active material layer) to collapse. Even when the electrode composite material is formed on the surface of the solid electrolyte layer, large cracks are generated in the electrode composite material, leading to detachment or peeling from the solid electrolyte layer.

[0030] As described above, the inventors initially conducted extensive research on improving the performance of all-solid-state sodium batteries by directly forming electrode composites on the surface of inorganic solid electrolytes. However, when electrodes are directly formed and integrated on the surface of inorganic solid electrolytes, there are problems with ionic conductivity between the active material precursor and the inorganic solid electrolyte. As a result, the battery resistance is currently high, and there are limitations to increasing the capacity per unit area. Therefore, in light of the need to produce electrode composites with high ionic conductivity, the inventors used polyphosphate transition metal oxide as the active material, coated or supported a resin-based binder on the surface of the polyphosphate transition metal oxide particles, and conducted extensive research to create composite particles that could be used to form batteries, leading to the present invention. The present invention can solve the conventional problems described above, as well as problems newly discovered by the inventors.

[0031] In view of these circumstances, the present invention provides a method for manufacturing an electrode mixture used in an all-solid-state sodium battery that can exhibit excellent charge-discharge cycle characteristics while maintaining a high discharge capacity at room temperature. The present invention also provides a method for manufacturing an all-solid-state sodium battery in which the electrode mixture obtained by the method for manufacturing the electrode mixture is used as the negative electrode and / or positive electrode. [Means for solving the problem]

[0032] To achieve the above-mentioned objective, the method for manufacturing an electrode composite material used in an all-solid-state sodium battery according to claim 1 is characterized by comprising: step A, which involves coating or supporting the resin-based binder on the surface of polyphosphate transition metal oxide particles to produce composite particles; step B, which involves filling the composite particles into a powder molding die and then applying pressure to obtain pellets; and step C, which involves thermally decomposing the resin-based binder contained in the pellets by heat treatment to create voids.

[0033] The invention according to claim 2 is characterized by comprising: step A, which involves coating or supporting a resin-based binder on the surface of polyphosphate transition metal oxide particles to produce composite particles; step B, which involves filling a powder molding die with the composite particles and then applying pressure to obtain pellets; step C, which involves thermally decomposing the resin-based binder contained in the pellets by heat treatment to create voids; and step D, which involves immersing or coating the pellets in a liquid containing at least one selected from the group consisting of ethylene carbonate, polyethylene carbonate, polyethylene glycol, and polyethylene oxide after step C, to fill all or part of the voids.

[0034] The invention according to claim 3 preferably involves a step A being a step of producing composite particles by drying a liquid in which a polyphosphate transition metal oxide and a resin-based binder are suspended in a solvent or dispersion medium.

[0035] The invention according to claim 4 is preferably such that step A is a step of producing the composite particles by a spray drying method or a fluid bed granulation method.

[0036] The invention according to claim 5 is preferably such that step B is a step of forming pellets by applying a pressure of 1 MPa to 100 MPa.

[0037] The invention according to claim 6 preferably involves step C being performed in an atmosphere of a mixed gas of at least an inert gas and a hydrogen gas, wherein, when the total volume of the mixed gas is 100 vol.%, the volume of the inert gas is in the range of 90 vol.% to 99.5 vol.%, and the volume of the hydrogen gas is in the range of 0.5 vol.% to 10 vol.%, and the resin binder is thermally decomposed while simultaneously softening and flowing the polyphosphate transition metal oxide.

[0038] The invention according to claim 7 preferably involves step C being a step of maintaining a temperature of 400°C to 2000°C for 5 minutes to 10 hours at a heating rate of 0.1°C / min to 50°C / min, thereby thermally decomposing the resin binder and simultaneously softening and flowing the polyphosphate transition metal oxide, thereby forming active material clusters in which multiple particles with a particle size in the range of 0.1 μm to 100 μm are linked together.

[0039] In the invention according to claim 8, it is preferable that the resin-based binder is polypropylene carbonate.

[0040] The invention according to claim 9 is characterized in that the thickness of the electrode mixture is 10 μm to 5000 μm, and the total weight of the electrode mixture per unit area is 1 mg / cm³. 2 ~5000 mg / cm³ 2 It is preferable that this is the case.

[0041] The method for manufacturing an all-solid-state sodium battery according to claim 10 is a method for manufacturing an all-solid-state sodium battery in which an organic solid electrolyte is interposed between an electrode mixture and an inorganic solid electrolyte, comprising: step A to produce composite particles by drying a liquid in which polyphosphate transition metal oxide and a resin-based binder are suspended in a solvent or dispersion medium, thereby coating or supporting the resin-based binder on the particle surface of the polyphosphate transition metal oxide; step B to obtain pellets by filling the composite particles into a powder molding die and then applying pressure; step C to thermally decompose the resin-based binder contained in the pellets by heat treatment; step D to fill all or part of the voids by immersing or coating the pellets in a liquid in which at least one selected from the group consisting of ethylene carbonate, polyethylene carbonate, polyethylene glycol, and polyethylene oxide is dissolved after step C; step E to coat the surface of the electrode mixture or the inorganic solid electrolyte with the organic solid electrolyte; and step F to bond the electrode mixture and the inorganic solid electrolyte together.

[0042] In the invention according to claim 11, it is preferable that the organic solid electrolyte is polyethylene glycol or polyethylene oxide with a molecular weight of 1,000 to 1,000,000.

[0043] The invention according to claim 12 preferably involves step E being a step of applying a liquid made by dissolving the organic solid electrolyte in a solvent and then drying it.

[0044] In the invention according to claim 13, it is preferable that steps A to E are performed in an environment with a dew point temperature of minus 40°C or lower.

[0045] The invention according to claim 14 is preferably an oxide-based solid electrolyte having a thickness of 1 mm or less and a porosity of 20% or less.

[0046] The invention according to claim 15 is preferably characterized in that the inorganic solid electrolyte is aluminum oxide containing sodium, and the carrier ion is sodium. [Effects of the Invention]

[0047] The invention according to claim 1 includes a step A of coating or supporting a resin-based binder on the surface of polyphosphate transition metal oxide particles to produce composite particles, a step B of filling a powder molding die with the composite particles and then applying pressure to obtain pellets, and a step C of thermally decomposing the resin-based binder contained in the pellets by heat treatment to create voids. Therefore, by coating or supporting a resin-based binder on the surface of the polyphosphate transition metal oxide, it becomes possible to pelletize at a pressure of 100 MPa or less. Furthermore, it is possible to improve the ionic conductivity between the solid electrolyte and the solid particles of the active material while ensuring the electronic conductivity of the electrodes, and to manufacture an electrode composite material for use in all-solid-state sodium batteries that can exhibit excellent charge-discharge cycle characteristics while maintaining a high discharge capacity at room temperature.

[0048] According to the invention of claim 2, the method for manufacturing an electrode composite used in an all-solid-state sodium battery comprises: step A, which involves coating or supporting a resin-based binder on the surface of polyphosphate transition metal oxide particles to produce composite particles; step B, which involves filling a powder molding die with the composite particles and then applying pressure to obtain pellets; step C, which involves thermally decomposing the resin-based binder contained in the pellets by heat treatment to create voids; and step D, which involves immersing or coating the pellets in a liquid containing at least one selected from the group consisting of ethylene carbonate, polyethylene carbonate, polyethylene glycol, and polyethylene oxide after step C, to fill all or part of the voids. As a result, it is possible to manufacture an electrode composite used in an all-solid-state sodium battery that can further enhance the ionic conductivity between the solid electrolyte and the solid particles of the active material while ensuring the electronic conductivity of the electrodes, and that can exhibit even better charge-discharge cycle characteristics while maintaining a high discharge capacity at room temperature.

[0049] According to the invention of claim 3, since step A is a step of producing composite particles by drying a liquid in which polyphosphate transition metal oxide and a resin-based binder are suspended in a solvent or dispersion medium, composite particles in which a resin-based binder is coated or supported on the surface of the polyphosphate transition metal oxide particles can be easily produced.

[0050] According to the invention of claim 4, since step A is a step of generating composite particles by spray drying or fluid bed granulation, composite particles can be easily generated by known granulation methods such as spray drying or fluid bed granulation.

[0051] According to the invention of claim 5, since step B is a step of pelletizing by applying a pressure of 1 MPa to 100 MPa, by pressurizing with such powder, the resin-based binders adhere to each other at a pressure of 1 MPa to 100 MPa, and dense pellets can be obtained.

[0052] According to the invention of claim 6, step C is performed in an atmosphere of a mixed gas of at least an inert gas and hydrogen gas, where, assuming the total volume of the mixed gas is 100 vol.%, the volume of the inert gas is in the range of 90 vol.% to 99.5 vol.%, and the volume of the hydrogen gas is in the range of 0.5 vol.% to 10 vol.%, and is a step in which the resin binder is thermally decomposed and the polyphosphate transition metal oxide is softened and flowed simultaneously. Therefore, when the volume of the inert gas and the volume of the hydrogen gas are within the above ranges, the resin binder can be easily thermally decomposed and the polyphosphate transition metal oxide can be easily softened and flowed simultaneously.

[0053] According to the invention of claim 7, step C is a step in which the resin binder is thermally decomposed and the polyphosphate transition metal oxide is softened and flowed at a heating rate of 0.1℃ / min to 50℃ / min, maintaining a temperature of 400℃ to 2000℃ for 5 minutes to 10 hours, thereby forming active material clusters in which multiple particles with particle sizes in the range of 0.1μm to 100μm are linked together. Therefore, when the temperature in step C is within the above range, the resin binder is thermally decomposed and the polyphosphate transition metal oxide is softened and flowed together, and active material clusters in which multiple particles with particle sizes in the range of 0.1μm to 100μm are linked together can be easily formed.

[0054] According to the invention of claim 8, since the resin binder is polypropylene carbonate, even in an inert or reducing environment, it is converted to carbon dioxide by heat treatment at 200°C or higher, disappearing without leaving any carbon behind, and having an extremely small impact on the electrode.

[0055] According to the invention of claim 9, the thickness of the electrode mixture is 10 μm to 5000 μm, and the total weight of the electrode mixture per unit area is 1 mg / cm³. 2 ~5000 mg / cm³ 2 Therefore, good battery input / output characteristics and energy density can be obtained.

[0056] According to the invention of claim 10, the process involves: step A, which involves drying a liquid in which polyphosphate transition metal oxide and a resin-based binder are suspended in a solvent or dispersion medium to coat or support the resin-based binder on the particle surface of the polyphosphate transition metal oxide to produce composite particles; step B, which involves filling the composite particles into a powder molding die and then applying pressure to obtain pellets; step C, which involves thermally decomposing the resin-based binder contained in the pellets by heat treatment; and after step C, a mixture of ethylene carbonate, polyethylene carbonate, polyethylene glycol, and polyethylene oxide from the group. The electrode mixture manufacturing process includes step D of immersing or coating the pellets in a liquid in which at least one selected substance is dissolved to fill all or part of the voids; step E of coating the surface of the electrode mixture or the inorganic solid electrolyte with the organic solid electrolyte; and step F of bonding the electrode mixture and the inorganic solid electrolyte together. As a result, an all-solid sodium storage battery can be manufactured using an electrode mixture obtained by the electrode mixture manufacturing method, which can exhibit excellent charge-discharge cycle characteristics while maintaining a high discharge capacity at room temperature, as the negative electrode and / or positive electrode.

[0057] According to the invention of claim 11, since the organic solid electrolyte is polyethylene glycol or polyethylene oxide with a molecular weight of 1,000 to 1,000,000, the organic solid electrolyte can have high functionality as an adhesive that binds the electrode mixture and the inorganic solid electrolyte.

[0058] According to the invention of claim 12, since step E is a step of applying a liquid made by dissolving an organic solid electrolyte in a solvent and then drying it, the organic solid electrolyte can be easily applied between the electrode mixture and the inorganic solid electrolytic chamber, and the organic solid electrolyte can make the adhesion between the electrode mixture and the inorganic solid electrolyte stronger.

[0059] According to the invention of claim 13, since steps A to E are performed in an environment with a dew point temperature of minus 40°C or lower, the electrode mixture obtained as described above can be sealed in a dry environment with a dew point of minus 40°C or lower, with the organic solid electrolyte in close contact with one surface of the inorganic solid electrolyte and the counter electrode provided on the other surface of the inorganic solid electrolyte.

[0060] According to the invention of claim 14, since the inorganic solid electrolyte is an oxide-based solid electrolyte with a thickness of 1 mm or less and a porosity of 20% or less, the energy density of the all-solid-state sodium battery becomes higher and the ionic conductivity becomes higher.

[0061] According to the invention of claim 15, since the inorganic solid electrolyte is aluminum oxide containing sodium and the carrier ion is sodium, the ionic conductivity can be further improved, and an all-solid-state sodium battery with excellent electrical insulation and heat resistance can be manufactured. [Brief explanation of the drawing]

[0062] [Figure 1] This figure shows a cross-sectional concept of an all-solid-state sodium battery according to one embodiment of the present invention. [Figure 2] This is a diagram illustrating the cross-sectional concept of an active material cluster contained in an electrode composite material. [Figure 3] This is a diagram illustrating the cross-sectional concept of an active material cluster contained in an electrode composite material. [Figure 4] This is a flowchart showing a method for manufacturing an electrode composite material according to one embodiment of the present invention. [Figure 5] This is a flowchart showing a method for manufacturing an all-solid-state sodium battery according to one embodiment of the present invention. [Figure 6] This is a conceptual diagram showing steps D to F in a method for manufacturing an all-solid-state sodium battery according to one embodiment of the present invention. [Figure 7] This is a cross-sectional conceptual diagram showing step F in a method for manufacturing an all-solid-state sodium battery according to one embodiment of the present invention. [Figure 8]This figure shows a cross-sectional concept of a bipolar all-solid-state sodium battery according to one embodiment of the present invention. [Figure 9] This figure compares the charging curves of Example 3 and Reference Example 2. [Modes for carrying out the invention]

[0063] Hereinafter, an all-solid-state sodium battery according to one embodiment of the present invention will be described in detail with reference to the attached drawings.

[0064] As shown in Figure 1, the all-solid-state sodium battery 1 according to this embodiment is constructed with an organic solid electrolyte 3 interposed between the electrode mixture 2 and the inorganic solid electrolyte 4.

[0065] The organic solid electrolyte 3 is a polyether or a derivative thereof obtained by polymerizing ethylene glycol, and is preferably composed of polyethylene glycol (PEG) or polyethylene oxide (PEO). In addition to its function as a solid electrolyte, the PEG or PEO also functions as an adhesive that binds the electrode mixture 2 and the inorganic solid electrolyte 4. While other substances, such as ethylene carbonate (EC), can also be used as the organic solid electrolyte, PEG or PEO are preferred because they have excellent adhesive properties.

[0066] Furthermore, the above PEG or PEO may contain sulfur compound functional groups, nitrogen compound functional groups, phosphorus compound functional groups, or acrylate functional groups. In addition, from the viewpoint of having a high function as an adhesive for bonding the electrode mixture and the inorganic solid electrolyte, the above PEG or PEO is preferably a polyether or derivative thereof obtained by polymerizing ethylene glycol with a weight-average molecular weight (Mw) of 1,000,000 or more.

[0067] In particular, when the electrode mixture 2 or the inorganic solid electrolyte 4 as the adherend has an uneven shape or voids on its surface, the organic solid electrolyte 3 penetrates into the unevenness and voids of the adherend, improving the contact area between the electrode mixture 2 and the inorganic solid electrolyte 4, thereby reducing the ionic resistance of the battery.

[0068] The organic solid electrolyte 3 is preferably liquefied and applied to the electrode mixture 2 or ( / and) the inorganic solid electrolyte 4. Also, the organic solid electrolyte 3 may be a non-flammable ionic liquid. The organic solid electrolyte 3 can be liquefied by dissolving the target material in an organic solvent. This organic solvent is not particularly limited as long as it can dissolve the target material, and examples include solvents such as chain hydrocarbon solvents and cyclic hydrocarbon solvents. Examples of chain hydrocarbon solvents include dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), tert-butyl isopropyl percarbonate, dichloromethane, nitrile-based, alcohol-based, etc. Examples of cyclic hydrocarbon solvents include N-methyl-2-pyrrolidone (NMP), ethylene sulfite, vinyl ethylene carbonate (VEC), propylene carbonate (PC), 1,3-dioxan-2-one, benzene, lactone-based, etc.

[0069] The non-flammable ionic liquid is not particularly limited as long as it has ionic conductivity. For example, in terms of the type of cation, non-flammable ionic liquids such as pyridine-based, alicyclic amine-based, aliphatic amine-based, etc. can be mentioned. By selecting the type of anion to be combined with this, various non-flammable ionic liquids can be synthesized. Examples of cations include imidazolium salts, pyridinium salts, phosphonium-based ions, inorganic ions, etc. Examples of anions include bromide ions, triflate, tetraphenylborate, hexafluorophosphate, etc.

[0070] The non-flammable ionic liquid is, for example, a cation such as imidazolinium and Br - 、Cl - 、BF4 - 、PF6 - 、(CF3SO2)2N - 、CF3SO3- FeCl4 - It can be obtained by known synthesis methods, such as by combining it with anions. Such a non-flammable ionic liquid can function as an electrolyte.

[0071] When assembling a battery, it is possible for the battery to function even if some of the above-mentioned organic solvents are present. However, it is preferable that they be sufficiently removed by reduced pressure or heat treatment to suppress the expansion of the battery due to the volatilization of the organic solvents. The removal method is not particularly limited, but for example, the drying method used for electrode slurries in lithium-ion batteries can be employed.

[0072] When the electrode mixture 2 or inorganic solid electrolyte 4, which is the adherend, is porous, the organic solid electrolyte 3 flows in through the pores on the adherend surface, which can significantly reduce the resistance (ionic resistance) caused by the ion conduction of the battery.

[0073] Furthermore, when the battery is overcharged, the organic solid electrolyte 3 undergoes oxidative decomposition of the PEG or PEO, suppressing a rise in battery voltage and eliminating its adhesive function. This also provides a shutdown function that separates the electrode composite material 2 and the inorganic solid electrolyte 4, thereby increasing the battery's impedance.

[0074] From the viewpoint of strongly bonding the electrode mixture 2 and the inorganic solid electrolyte 4, a higher molecular weight of the PEG or PEO is preferable. However, if the weight-average molecular weight exceeds 1 million, the viscosity becomes too high, making it difficult to handle, and the ionic conductivity decreases when a sodium salt, as described later, is added. Conversely, if the weight-average molecular weight is less than 1000, the adhesion is poor, and when the battery is subjected to vibration or shock, the interface between the electrode mixture 2 and the inorganic solid electrolyte 4 is easily destroyed, which tends to increase the impedance of the battery. Also, low molecular weights exhibit hygroscopicity, and the drying process takes a long time. Therefore, the weight-average molecular weight is preferably 1000 or more, with an upper limit of 1 million, and more preferably 2500 or more. These can be crosslinked or non-crosslinked.

[0075] The weight-average molecular weight can be determined, for example, by measuring it using gel permeation chromatography (GPC) with liquid chromatography.

[0076] The inorganic solid electrolyte 4 can be sulfide-based, oxide-based, or hydride-based, and one type may be used alone, or two or more types may be used in combination. From the viewpoint of increasing the energy density of the battery and improving ionic conductivity, such inorganic solid electrolyte 4 is preferably 1 mm or less in thickness and 20% or less in porosity.

[0077] Examples of sulfide-based compounds include A4SiS4, A4GeS4, A3PS4, and A 9.54 Si 1.74 P 1.44 S 11.7 C l0.3 , A 10 GeP2S 12 , A 3.25 Ge 0.25 P 0.75 S4, A6PS5Cl, A2S-B2S3·AI, A2S-P2S5-ABH4, A2S-SiS2·A4SiO4, A2S-P2S5, A7P3S 11 , A 3.25 P 0.95 Examples include S4 (where A represents Na or other alkali metal elements containing Na).

[0078] Oxide systems include, for example, A 1.3 Al 0.3 Ti 1.7 (PO4)3, A 0.34 La 0.51 TiO 2.94 A7LaZr2O 12 , A4SiO4·A2BO3, A3PO4-A4SiO4, A3BO3-A2SiO4, A3BO3-A2SO4, A 2.9 PO 3.3 N 0.46 , A 1.07 Al 0.69 Ti 1.46 (PO4)3, A 3.3 PO 3.8 N0.22 , A 2.9 PO 3.3 N 0.46 (A represents Na or other alkali metal elements containing Na), aluminum oxide containing sodium, NASICON crystal (Na 1+x Zr2SixP 3-x O 12 , 0 < x < 3), etc. can be mentioned.

[0079] In the hydride system, for example, ABH4, ABH4 - AI, ABH4 - ABr, ABH4 - AF, ABH4 - ACl, etc. can be mentioned (A represents an alkali metal element).

[0080] Also, it is preferable that the above inorganic solid electrolyte 4 is within the range of porosity of 0% to 2:0%. That is, an inorganic solid electrolyte as dense as possible is acceptable. By making the porosity 20% or less, the ionic conductivity can be increased. Conversely, when the porosity exceeds 20%, the ionic conductivity is poor, and micro short - circuits are likely to occur during charging.

[0081] In other words, it is preferable that the above inorganic solid electrolyte 4 is within the range of density of 2.7 g / cc to 3.5 g / cc. If it is less than 2.7 g / cc, there are too many voids, resulting in poor ionic conductivity, and micro short - circuits are likely to occur during charging.

[0082] However, the production of the inorganic solid electrolyte 4 with a porosity of 0% is not practical except by using single crystals. Therefore, it is preferable to infiltrate the organic solid electrolyte 3 into the voids of the inorganic solid electrolyte 4 to further improve the ionic conductivity. Here, when the density of the inorganic solid electrolyte 4 exceeds 3.5 g / cc, it becomes difficult for the organic solid electrolyte 3 to infiltrate, so it is preferably 3.5 g / cc or less.

[0083] Note that the above density is the density when the inorganic solid electrolyte 4 is filled in a container of a certain volume and its internal volume is used as the volume, and more precisely, it means the bulk density.

[0084] There are no particular restrictions on the shape, but it is acceptable as long as it is molded into one of the following forms: film, sheet, pellet, or ribbon.

[0085] Furthermore, the inorganic solid electrolyte 4 is preferably an oxide-based material, from the viewpoint of not generating toxic gases when it comes into contact with water. Among these, aluminum oxide containing sodium is preferred because it has excellent electrical insulation properties and heat resistance.

[0086] Sodium-containing aluminum oxide is a crystal or ceramic material represented by the general formula Na2O-xAl2O3 (x=2~20), with a structure in which sodium ions are distributed between two-dimensional layers formed by alumina blocks. Depending on how the alumina blocks are stacked, β-alumina (Na2O-11Al2O3) and β"-alumina (β-double-primed alumina (Na2O-5Al2O3)) are known, but in either case, sodium ions move between the two-dimensional layers formed by the alumina blocks, so it functions as a solid electrolyte.

[0087] Aluminum oxide containing sodium can be synthesized, for example, by calcining a mixture of α-alumina (Al2O3) and sodium carbonate at 1100°C to 1500°C.

[0088] Sodium-containing aluminum oxide preferably further contains at least one metal or oxide selected from Mg, Li, K, Rb, Zr, Pb, Y, Ag, Tl, Sr, Ca, and Fe. The content of these metals is preferably 5 vol.% or less relative to the sodium-containing aluminum oxide. This makes it easier to obtain dense sodium-containing aluminum oxide, further improving its ionic conductivity.

[0089] The inorganic solid electrolyte 4 described above may also be included in the electrode mixture 2 as a powder with a particle size of 0.1 μm to 100 μm.

[0090] Furthermore, in the all-solid-state sodium battery 1 according to the present invention, it is preferable that the electrode mixture 2 contains, in addition to the active material, at least one selected from ethylene carbonate (EC), polyethylene carbonate (PEC), polyethylene glycol (PEG), and polyethylene oxide (PEO).

[0091] By including at least one of EC, PEC, PEG, and PEO as an ion conduction aid in electrode mixture 2, the ionic resistance of the electrode mixture can be reduced. Note that the EC, PEC, PEG, and PEO included in electrode mixture 2 as ion conduction aids may be modified in terms of their functional groups to the extent that their structure and properties are not significantly altered (i.e., derivatives are acceptable). Depending on the mass of electrode mixture 2, the amount of EC, PEC, PEG, and PEO included in electrode mixture 2 as ion conduction aids should be 0.1 mg / cm³. 2 ~500mg / cm 2 It is preferably within the range of 0.2 mg / cm³. 2 ~250 mg / cm³ 2 It is more preferable that it be within the range of 0.5 mg / cm³. 2 ~100mg / cm 2 It is even more preferable that this be the case.

[0092] In this configuration, a material selected from EC, PEC, PEG, and PEO, which is included in the electrode mixture 2 as an ion conduction aid, functions as an electrolyte that improves the ion conductivity in the electrode mixture 2. Furthermore, the organic solid electrolyte 3 interposed between the electrode mixture 2 and the inorganic solid electrolyte 4 fuses with the electrode mixture 2 to form a single unit, resulting in a battery with low impedance. As a result, even when forming an electrode mixture 2 with a large thickness, an all-solid-state sodium battery can be obtained that exhibits excellent charge-discharge cycle characteristics while maintaining a high discharge capacity at room temperature.

[0093] Furthermore, when the battery is overcharged, a material selected from EC, PEC, PEG, and PEO contained in the electrode composite 2 is oxidatively decomposed, providing a function to suppress the rise in battery voltage.

[0094] Among the materials selected from EC, PEC, PEG, and PEO contained in the electrode composite material 2, from the viewpoints of excellent heat resistance of the electrode composite material 2, high ionic conductivity, and easy fusion with the organic solid electrolyte 3 interposed between the electrode composite material 2 and the inorganic solid electrolyte 4, a polymer material having a molecular weight of 500 or more selected from PEC, PEG, and PEO is preferable, and more preferably PEG or PEO. However, in the case of a polymer material having a molecular weight exceeding 200,000, the viscosity becomes too high, making it difficult to incorporate it into the electrode composite material by the manufacturing method described later, and the ionic conductivity of the electrode composite material 2 decreases. Note that these may be crosslinked or non-crosslinked.

[0095] The electrode composite material 2 includes a positive electrode composite material (positive electrode active material layer) and a negative electrode composite material (negative electrode active material layer). In the present invention, it is preferable that any of the electrode composite materials contains a polyphosphate transition metal oxide. In particular, when the electrode composite material 2 is used as a positive electrode composite material, the polyphosphate transition metal oxide functions as an active material.

[0096] The polyphosphate transition metal oxide is preferably a crystal represented by the general formula Na a M b P c O d .

[0097] From the viewpoints of high ionic conductivity, charge-discharge capacity, or output characteristics of the polyphosphate transition metal oxide, 0.0 < a ≤ 3.5, b = 1, 1.0 ≤ c ≤ 3.0, 3.0 ≤ d ≤ 30, and M is preferably at least one element selected from Fe, Mn, Co, Ni, and V.

[0098] Specifically, Na2FeP2O7, Na3Fe2(PO4)3, NaFe3P3O 12 , Na2Fe3(PO4)3, Na4Fe3(PO4)2(P2O7), Na2MnP2O7, Na2CoP2O7, Na2NiP2O7, Na2Fe 0.5 Mn 0.5 P2O7, Na3V2(PO4)3, NaVOPO4, Na9V3(P2O7)3(PO4)2, etc. may be mentioned, and one or more of these may be used.

[0099] Among the above polyphosphoric acid transition metal oxides, glass or crystallized glass is easy to synthesize as a polyphosphoric acid transition metal oxide precursor, and it has the characteristics of softening and flowing and being easy to crystallize during the firing (heat treatment) process at 700 °C or lower. Therefore, 0.0 < a ≤ 3.0, b = 1, 1.1 ≤ c ≤ 2.9, 3.5 ≤ d ≤ 12 is more preferable, 0.7 ≤ a ≤ 2.4, b = 1, 1.2 ≤ c ≤ 2.8, 4.0 ≤ d ≤ 11 is further preferable, and 1.7 ≤ a ≤ 2.3, b = 1, 1.4 ≤ c ≤ 2.7, 5.0 ≤ d ≤ 10 is most preferable.

[0100] In the polyphosphoric acid transition metal oxide, part of the Na sites of the above materials may be substituted with Li or K, or the materials may be those in which part of the O sites (octahedral positions) and P sites (octahedral positions) are substituted with F, Cl, S, or B.

[0101] In addition to the polyphosphoric acid transition metal oxide, the electrode composite material 2 may further contain active materials used in sodium ion batteries, sodium metal batteries, sodium air batteries, sodium-sulfur batteries, sodium-metal chloride batteries, all-solid sodium storage batteries, etc. That is, in addition to the polyphosphoric acid transition metal oxide, it may contain known sodium metal, known sodium alloy or known sodium ion occlusion material.

[0102] When the electrode composite material 2 is used as a positive electrode composite material, other positive electrode active materials may be further contained in addition to the polyphosphoric acid transition metal oxide. Known materials including transition metal oxide systems, sulfur systems, solid solution systems, etc. are used as the positive electrode active materials. When the electrode composite material 2 is used as a negative electrode composite material, since a practical energy density cannot be obtained only with the polyphosphoric acid transition metal oxide, it is preferable to further contain other negative electrode active materials in addition to the polyphosphoric acid transition metal oxide.

[0103] The negative electrode active material preferably includes known materials including transition metal oxide systems, sulfur systems, sodium metal, materials alloyed with sodium, or materials capable of reversibly occluding and releasing sodium ions.

[0104] The electrode active material (positive electrode active material or negative electrode active material) described above is not particularly limited in shape, but it is preferable that it has a structure in which multiple particles of the active material, with a particle size in the range of 0.1 μm to 100 μm, are linked together by crystalline polyphosphate transition metal oxide. In other words, it is preferable that the electrode composite material forms active material clusters in which multiple particles with a particle size in the range of 0.1 μm to 100 μm are linked together.

[0105] Here, particle size refers to the median diameter (D50) on a volume basis in laser diffraction-scattering particle size distribution analysis.

[0106] Furthermore, it is preferable that the electrode mixture 2 contains a conductive additive. The conductive additive is not particularly limited as long as it has electronic conductivity, and examples include metals, carbon materials, conductive polymers, conductive glass, etc., but carbon materials are preferred from the viewpoint of high electronic conductivity and low specific gravity. Specifically, examples include acetylene black (AB), Ketjen black (KB), furnace black (FB), thermal black, lamp black, channel black, roller black, disc black, carbon black (CB), glassy carbon, etc., and one or more of these may be used.

[0107] Of these, conductive additives with a primary particle size in the range of 1 nm to 100 nm are preferred. With this type of carbon, if the electrode composite 2 forms active material clusters in which multiple individual particles are linked together, as shown in Figure 2, carbon can be incorporated into the parts (polyphosphate transition metal oxide crystals 9) that connect the individual particles (electrode active material particles 8) to each other. With this configuration, the electrical conductivity between the active material particles is improved by the conductive additive carbon. As a result, the output characteristics of the battery are greatly improved.

[0108] Furthermore, the specific surface area of ​​carbon for nitrogen adsorption is 20 m². 2 / g~500m 2It is preferable that the conductive additive is within the range of / g. If this carbon is used, and the electrode composite 2 forms active material clusters in which multiple individual particles are linked together, then, as shown in Figure 3, the carbon can be supported on the surface of the portion (polyphosphate transition metal oxide crystal 9) that connects the individual particles (electrode active material particles 8) to the individual particles (electrode active material particles 8). With this configuration, the conductive additive carbon is present in the linkage portion between the active material particles, thus improving the electronic conductivity of the electrode composite. As a result, the output characteristics of the battery are greatly improved.

[0109] Preferably, the conductive additive described above further includes fibrous carbon with a fiber diameter in the range of 1 nm to 300 nm or flake-shaped carbon with a thickness in the range of 1 nm to 300 nm. This makes it less likely for the conductive network to break when the electrode composite undergoes volume changes during charging and discharging, thereby improving the battery's cycle life characteristics.

[0110] Here, fiber diameter refers to the diameter observed when the cross-section of fibrous carbon is viewed with a transmission electron microscope (TEM). Thickness refers to the thickness observed when the cross-section of flake-shaped carbon is viewed with a transmission electron microscope (TEM).

[0111] Examples of fibrous carbon include carbon fibers (for example, vapor-grown carbon fibers known as VGCF, a registered trademark) and carbon nanotubes (CNTs). Examples of flake-like carbon include thin-flake graphite and graphene.

[0112] The conductive additive contained in the electrode mixture 2 is preferably present in an amount of 0.5 to 30% by mass relative to the electrode mixture 2.

[0113] Next, the manufacturing method of the electrode composite material 2 used in the all-solid-state sodium battery 1 will be described in detail with reference to the attached drawings.

[0114] The electrode composite material 2 described above can be manufactured by filling a powder containing at least a polyphosphate transition metal oxide into a powder molding die, applying pressure to form pellets (tablets), and then firing the pellets at a temperature of 400°C to 2000°C in an inert gas or reducing gas atmosphere.

[0115] More specifically, the method for manufacturing the electrode composite material 2 used in the all-solid-state sodium battery 1, as shown in Figure 4, includes: step A, which involves drying a liquid in which polyphosphate transition metal oxide and resin-based binder are suspended in a solvent or dispersion medium to coat or support the resin-based binder on the particle surface of the polyphosphate transition metal oxide to produce composite particles; step B, which involves filling a powder molding die with the composite particles and then applying pressure to obtain pellets; and step C, which involves thermal decomposition of the resin-based binder contained in the pellets by heat treatment to create voids.

[0116] Furthermore, the method for manufacturing the electrode mixture 2 used in the all-solid-state sodium battery 1 includes, after step C, step D, in which pellets are immersed in or coated with a liquid in which at least one selected from the group consisting of ethylene carbonate, polyethylene carbonate, polyethylene glycol, and polyethylene oxide is dissolved, thereby filling all or part of the voids.

[0117] Polyphosphate transition metal oxides coated with a resin-based binder are obtained by adding a solvent to a mixed powder consisting of polyphosphate transition metal oxide and a resin-based binder, mixing the mixture, volatilizing and removing the solvent, and then grinding or classifying the mixture. Unless the solvent is water, it is preferable to carry out the work in a dry environment (dew point below -40°C).

[0118] For preparing the above-mentioned mixed powders and for mixing them with solvents, known mixing methods can be used, such as rolling mills, vibrating mills, planetary mills, oscillating mills, horizontal mills, attritor mills, jet mills, grinders, homogenizers, fluidizers, paint shakers, and mixers.

[0119] Furthermore, known granulation methods can be applied to remove the solvent by volatilization and then pulverize or classify the mixture. Examples include fluidized bed granulation, agitated pulverization, rolling granulation, spray drying, extrusion granulation, and coating granulation. Of these, spray drying and fluidized bed granulation are particularly preferred.

[0120] In the spray-drying method, for example, a suspension in which polyphosphate transition metal oxide and a resin-based binder are dispersed is sprayed from above into a greenhouse heated to 50-300°C at a rate of 1-30 mL / min and an air pressure of 0.01-5 MPa to create aggregated granules, which are then dried to obtain granules.

[0121] In the fluidized bed granulation method, for example, powdered raw materials are placed in a fluidized bed granulator, and hot air heated to 50-300°C is introduced from below to fluidize and mix the powdered raw materials (granule precursor). A liquid containing a resin-based binder dissolved or dispersed in this mixed powdered raw material is then sprayed from above using a nozzle. By uniformly spraying the resin-based binder onto the powder surface at a rate of 1-30 mL / min and an air pressure of 0.01-5 MPa, aggregated granules are formed, and these are then dried to obtain the granulated product.

[0122] In this embodiment, step B is a step in which pellet molding is performed by applying a pressure of 1 MPa to 100 MPa.

[0123] In the above-mentioned resin-based binder, when the total of the polyphosphate transition metal oxide and the resin-based binder is 100% by mass, the resin-based binder is preferably in the range of 0.5 to 40% by mass, and more preferably in the range of 1 to 35% by mass.

[0124] By using this type of powder and applying pressure molding, the resin-based binders adhere to each other at pressures of 1 MPa to 100 MPa, resulting in dense pellets. At pressures below 1 MPa, the resin-based binders do not adhere well to each other. On the other hand, at pressures exceeding 100 MPa, the equipment becomes large and complex.

[0125] Pelleting polyphosphate transition metal oxide powder requires high pressures exceeding 100 MPa, necessitating large-scale pressure equipment. Therefore, the above-mentioned polyphosphate transition metal oxide is coated or supported with a resin-based binder. By coating or supporting the surface of the polyphosphate transition metal oxide with a resin-based binder, pelletization becomes possible at pressures below 100 MPa.

[0126] In this embodiment, step C is a step in which the resin binder is thermally decomposed and the polyphosphate transition metal oxide is softened and flowed in an atmosphere of a mixed gas of at least an inert gas and hydrogen gas, where the total volume of the mixed gas is 100 vol.%, the volume of the inert gas is in the range of 90 vol.% to 99.5 vol.%, and the volume of the hydrogen gas is in the range of 0.5 vol.% to 10 vol.%.

[0127] Furthermore, step C is a process in which the resin binder is thermally decomposed and the polyphosphate transition metal oxide is softened and flowed at a heating rate of 0.1°C / min to 50°C / min for more than 5 minutes and less than 10 hours, thereby forming active material clusters in which multiple individual particles with a particle size in the range of 0.1 μm to 100 μm are linked together.

[0128] The resulting pellets are further fired in a reducing gas atmosphere containing an inert gas, which softens and fluidizes the polyphosphate transition metal oxide, resulting in an integrated electrode composite. Simultaneously, the resin-based binder is thermally decomposed. Therefore, the electrode composite (pellets after firing) does not contain resin, and a porous electrode composite with a void ratio in the range of 5% to 50% is obtained.

[0129] In this embodiment, it is preferable that the all-solid-state sodium battery 1 does not contain a resin-based binder in the electrode mixture 2. This means that although the intermediate product contains a resin-based binder, it is burned away during firing and therefore not present in the final product. The inclusion of a resin-based binder in the electrode mixture 2 increases both electronic and ionic resistance.

[0130] Resin-based binders are binders for compounds with carbon as the main molecular backbone. Examples include polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyimide (PI), polyamide, polyamide-imide, polyacrylic, styrene-butadiene rubber (SBR), ethylene-vinyl acetate copolymer (EVA), polypropylene carbonate (PPC), styrene-ethylene-butylene-styrene copolymer (SEBS), carboxymethylcellulose (CMC), xanthan gum, polyvinyl alcohol (PVA), polyvinyl butyral (PVB), ethylene vinyl alcohol, polyethylene (PE), polypropylene (PP), polyacrylic acid, lithium polyacrylate, sodium polyacrylate, potassium polyacrylate, ammonium polyacrylate, methyl polyacrylate, and polyacrylic acid. Examples of materials include ethyl lylate, polyacrylate amine, polyacrylic acid ester, epoxy resin, polyethylene terephthalate (PET), polybutylene terephthalate (PBT), nylon, vinyl chloride, silicone rubber, nitrile rubber, cyanoacrylate, urea resin, melamine resin, phenolic resin, latex, polyurethane, silylated urethane, nitrocellulose, dextrin, polyvinylpyrrolidone, vinyl acetate, polystyrene, chloropropylene, resorcinol resin, polyaromatic, modified silicone, methacrylic resin, polybutene, butyl rubber, 2-propenoic acid, cyanoacrylic acid, methyl methacrylate, glycidyl methacrylate, acrylic oligomer, 2-hydroxyethyl acrylate, polyacetal, alginic acid, starch, sucrose, lacquer, animal glue, and casein.

[0131] In this embodiment, the resin-based binder is polypropylene carbonate (PPC).

[0132] Many of the resin-based binders mentioned above undergo thermal decomposition and carbonization at temperatures above 150°C, but polypropylene carbonate (PPC) is preferable because, even in inert or reducing environments, it transforms into carbon dioxide through heat treatment at temperatures above 200°C, disappearing without leaving any carbon residue, thus having very little impact on electrodes. The carbon generated by the thermal decomposition of resin-based binders has low conductivity unless fired at high temperatures, which can adversely affect electrodes.

[0133] In electrode composites that include polyphosphate transition metal oxides, as well as active materials used in sodium-ion batteries, sodium-metal batteries, sodium-air batteries, sodium-sulfur batteries, sodium-metal chloride batteries, and all-solid-state sodium batteries, it is preferable to coat or support not only the polyphosphate transition metal oxides but also these active materials with a resin-based binder. The same applies when a conductive additive is added.

[0134] The firing conditions are not particularly limited as long as the temperature is maintained within the range of 400°C to 2000°C for 5 minutes or more under a reducing gas atmosphere containing an inert gas. However, from the viewpoint of softening and flowing the polyphosphate transition metal oxide and thermally decomposing the resin binder, it is preferable to raise the temperature within the range of 0.1°C / min to 50°C / min, maintain the temperature at 400°C to 2000°C, and maintain it for 5 minutes to 10 hours.

[0135] After firing, the electrode composite material should have a thickness of 10 μm to 5000 μm and a total weight of 1 mg to 5000 mg / cm², from the perspective of battery input / output characteristics and energy density. 2 It is preferable that the electrode composite material after firing has a thickness in the range of 200 μm to 4000 μm and a total weight per unit area of ​​160 mg to 4800 mg / cm². 2 It is more preferable that the electrode composite material after firing has a thickness in the range of 500 μm to 3000 μm and a total weight per unit area of ​​400 mg to 3600 mg / cm². 2 It is even more preferable that it be within the range.

[0136] To include materials selected from EC, PEC, PEG, and PEO in electrode composite 2, it is possible to mix these materials with the active material and pelletize them. However, if the composite is manufactured by firing polycrystalline glass or glass of polyphosphate transition metal oxide to generate crystals of polyphosphate transition metal oxide, firing with EC, PEC, PEG, and PEO already included will cause thermal decomposition, making it impossible to include EC, PEC, PEG, and PEO in the composite. Therefore, it is necessary to include materials such as EC, PEC, PEG, and PEO after firing the polycrystalline glass or glass of polyphosphate transition metal oxide.

[0137] Therefore, by liquefying EC, PEC, PEG, PEO, etc., and applying it to the calcined polyphosphate transition metal oxide, or by immersing the calcined polyphosphate transition metal oxide in a liquefied solution of EC, PEC, PEG, PEO, etc., the electrode composite can be made to contain a material selected from EC, PEC, PEG, and PEO.

[0138] For liquefaction of EC, PEC, PEG, PEO, etc., the temperature of the target material may be increased, but it is preferable to add an organic solvent for liquefaction. This organic solvent is not particularly limited as long as it can dissolve and liquefy the target material. Examples include linear hydrocarbon solvents (DMC, DEC, EMC, dichloromethane, alcohol-based solvents, etc.) and cyclic hydrocarbon solvents (NMP, benzene, lactone-based solvents, etc.). It is preferable to remove the organic solvent by reducing the pressure or by heat treatment. For example, a drying method for electrode slurries used in lithium-ion batteries can be employed.

[0139] When the electrode mixture 2 is thick, simply coating it with liquefied EC, PEC, PEG, or PEO will not allow for sufficient penetration. Therefore, it is preferable to immerse the calcined polyphosphate transition metal oxide in liquefied EC, PEC, PEG, or PEO. In this state, further reducing the pressure allows the liquefied material to penetrate deep into the pores of the calcined polyphosphate transition metal oxide. The reduced pressure environment can be created by lowering the pressure below atmospheric pressure (negative pressure). For example, a negative pressure environment of 0 MPa to -0.1 MPa can be created using a vacuum pump.

[0140] The electrode mixture 2 described above is preferably porous with a porosity in the range of 5% to 50%, excluding the material selected from EC, PEC, PEG, and PEO contained in the electrode mixture 2. If the porosity is less than 5%, it is not possible to sufficiently incorporate EC, PEC, PEG, and PEO into the electrode mixture. If it exceeds 50%, it is possible to include a large amount of EC, PEC, PEG, and PEO in the electrode mixture, but the proportion of active material in the electrode mixture 2 will be small, resulting in a lower energy density.

[0141] Here, porosity is a value calculated from the apparent density of the object and the true density of the constituent material using the following formula: porosity (%) = 100 - (apparent density of the object / true density of the constituent material) × 100.

[0142] Furthermore, the electrode mixture 2 is preferably porous, having multiple pores with a diameter of 0.1 μm to 100 μm, excluding the material selected from EC, PEC, PEG, and PEO contained in the electrode mixture 2. If the pore diameter is outside this range, it becomes difficult to sufficiently incorporate EC, PEC, PEG, PEO, etc. into the electrode mixture 2 in the manufacturing method of the electrode mixture 2. In other words, if the pore diameter is less than 0.1 μm, EC, PEC, PEG, PEO, etc. do not easily penetrate the electrode mixture, and conversely, if it exceeds 100 μm, the strength of the electrode mixture 2 is low and it becomes easily damaged.

[0143] The all-solid-state sodium battery 1 according to this embodiment can be manufactured, for example, by sealing the electrode mixture 2 obtained as described above in a dry environment with a dew point of minus 40°C or lower, in close contact with one surface of the inorganic solid electrolyte 4 via the organic solid electrolyte 3, with a counter electrode provided on the other surface of the inorganic solid electrolyte 4.

[0144] More specifically, the manufacturing method for the all-solid-state sodium battery according to this embodiment, as shown in Figures 5 to 7, comprises: Step A, which involves drying a liquid in which polyphosphate transition metal oxide and resin-based binder are suspended in a solvent or dispersion medium to coat or support the resin-based binder on the particle surface of the polyphosphate transition metal oxide to produce composite particles; Step B, which involves filling a powder molding die with the composite particles and then applying pressure to obtain pellets; Step C, which involves thermally decomposing the resin-based binder contained in the pellets by heat treatment; and Step D, which involves immersing or coating the pellets in a liquid in which at least one selected from the group consisting of ethylene carbonate, polyethylene carbonate, polyethylene glycol, and polyethylene oxide is dissolved after Step C to fill all or part of the voids; Step E, which involves coating the surface of the electrode mixture or inorganic solid electrolyte with an organic solid electrolyte; and Step F, which involves bonding the electrode mixture and the inorganic solid electrolyte. Figure 6 is a conceptual diagram showing Steps D to F. Figure 7 is a cross-sectional conceptual diagram showing Step F.

[0145] Furthermore, in this embodiment, step E is a step in which an organic solid electrolyte is dissolved in a solvent to make it liquid, which is then applied and dried. Steps A to E are performed in an environment with a dew point temperature of minus 40°C or lower.

[0146] In this embodiment, the inorganic solid electrolyte is an oxide-based solid electrolyte with a thickness of 1 mm or less and a porosity of 20% or less. The inorganic solid electrolyte is aluminum oxide containing sodium, and the carrier ion is sodium.

[0147] There are no particular restrictions on the counter electrode. When electrode mixture 3 is used as the positive electrode mixture, the counter electrode can be an electrode mixture containing a negative electrode active material, a known sodium metal negative electrode, a known sodium alloy negative electrode, or a known sodium ion storage negative electrode. When electrode mixture 3 is used as the negative electrode mixture, the counter electrode can be a positive electrode mixture, a known sodium alloy positive electrode, or a known sodium ion storage positive electrode.

[0148] Furthermore, it is preferable that the all-solid-state sodium battery 1 is also configured with the above-mentioned organic solid electrolyte 3 between the counter electrode and the inorganic solid electrolyte 4.

[0149] Furthermore, the all-solid-state sodium battery 1 according to the present invention preferably has a structure in which the electrode mixture 2 is in electrical contact with an electronically conductive current collector 6. The current collector 6 may be a metal with through holes or a non-through metal, but by using a non-through metal, an all-solid-state battery with a bipolar structure as shown in Figure 8 can be manufactured. The bipolar electrode may be manufactured by bringing a current collector 6 made of a non-through metal such as a metal foil or metal plate into contact with the electrode mixture 2, or it may be obtained by forming the current collector 6 on the electrode mixture 2 by methods such as electroplating or vapor phase growth. With an all-solid-state battery with a bipolar structure, a high voltage can be obtained with a single cell.

[0150] On the other hand, when using a metal with through holes as the current collector, current can be collected three-dimensionally from the electrode composite material by filling the current collector with the electrode composite material. This improves the electronic conductivity of the electrode composite material, resulting in a battery with excellent output characteristics.

[0151] As described above, an all-solid-state sodium battery has been explained, but various additions, modifications, or deletions are possible without departing from the spirit of the present invention. For example, the electrolyte of the all-solid-state sodium battery of the present invention may be further enriched with an electrolyte solution, an ionic liquid, or a gel electrolyte. For example, the carrier ions of the battery may be changed from sodium ions to other alkali metal ions (such as lithium ions or potassium ions) to form an all-solid-state lithium-ion battery or an all-solid-state potassium-ion battery.

[0152] One embodiment of the present invention is characterized by comprising the all-solid-state sodium storage battery of the present invention. That is, the all-solid-state sodium storage batteries of the present invention are directly connected to each other or electrically connected via a busbar, and the battery group consists of two or more single cells.

[0153] An electrical device according to one embodiment of the present invention is characterized by comprising an all-solid-state sodium storage battery or battery pack of the present invention.

[0154] Electrical appliances include, for example, irons, whisks, all-in-one computers, clothes dryers, medical equipment, intercoms, wearable devices, video equipment, air conditioners, air circulators, gardening machinery, motorcycles, ovens, music players, music recorders, hot air heaters, toys, car stereos, flashlights, loudspeakers, car navigation systems, portable gas stoves, home battery storage systems, nursing care equipment, humidifiers, dryers, gas pumps, water dispensers, suction machines, safes, glue guns, mobile phones, personal information devices, air purifiers, air-conditioned clothing, game consoles, fluorescent lights, lint removers, cordless phones, coffee makers, and coffee. - Warmers, ice shavers, kotatsu (heated tables), photocopiers, hair cutting equipment, shavers, lawnmowers, automobiles, lighting fixtures, dehumidifiers, sealers, shredders, automated external defibrillators, rice cookers, stereos, stoves, speakers, trouser presses, smartphones, rice polishing machines, washing machines, bidet toilet seats, sensors, electric fans, submarines, blowers, vacuum cleaners, flying cars, tablets, body fat scales, fishing gear, digital cameras, televisions, television sets, video games, displays, disc changers, desktop computers, railways, televisions, electric carpets, desk lamps, electric stoves Electric kettles, electric blankets, calculators, electric carts, electric wheelchairs, power tools, electric cars, electric floats, electric toothbrushes, telephones, electric bicycles, electric insect killers, induction cookers, electronic organizers, electronic musical instruments, electronic locks, electronic cards, microwave ovens, electronic mosquito repellents, e-cigarettes, telephones, power load levelers, toasters, hair dryers, transceivers, clocks, drones, food waste disposers, laptops, incandescent light bulbs, soldering irons, panel heaters, halogen heaters, fermenters, bread makers, hybrid cars, personal computers, computer peripherals, hair clippers, panel heaters, video cameras, video devices Buckets, airplanes, emergency lights, emergency batteries, ships, beauty equipment, printers, photocopiers, crushers, sprayers, fax machines, forklifts, plug-in hybrid vehicles, projectors, hair dryers, hair irons, headphones, disaster prevention equipment, security equipment, home theaters, hot sandwich makers, hot plates, pumps, air fresheners, massage machines, mixers, mills, movie players, monitors, mochi makers, water heaters, underfloor heating panels, radios, radio cassette players, lanterns, remote control devices, laminators, remote controls, microwave ovens, water coolers, refrigerators, air coolers, evaporative coolers,Examples include air conditioners, robots, word processors, and GPS devices. [Examples]

[0155] The following describes embodiments of the present invention in more detail, but the present invention is not limited to these embodiments. In particular, the embodiments describe an all-solid-state sodium battery using β''-alumina as the solid electrolyte, but the present invention is not limited to this. Also, the active material contained in the electrode mixture is described using Na2FeP2O7 as an example, but the present invention is not limited to this.

[0156] <Preparation of positive electrode active material precursor powder> The cathode active material precursor was prepared by a melt-and-cooling method. Sodium metaphosphate (NaPO3), iron oxide (Fe2O3), and orthophosphoric acid (H3PO4) were mixed as raw materials in a molar ratio of 40Na2O-20Fe2O3-40P2O5 and melted at 1350°C for 1 hour in an atmospheric environment. The resulting molten glass was poured between a pair of cooling rollers and molded while rapidly cooling to obtain a film-like glass body with a thickness of 0.1 to 1 mm. This glass body was subjected to ball mill grinding using φ20 mm ZrO2 pebbles for 10 hours and passed through a resin sieve with a mesh size of 120 μm to obtain a coarse glass powder with an average particle size of 7 μm. Furthermore, this coarse glass powder was subjected to ball mill grinding using φ3 mm ZrO2 pebbles with ethanol as a grinding aid for 80 hours to obtain glass powder (cathode active material precursor powder) with an average particle size of 0.6 μm. Powder X-ray diffraction measurements confirmed that the glass powder is amorphous.

[0157] <Preparation of positive electrode active material powder> The glass body obtained above was crystallized by firing at 650°C for 1 hour in a nitrogen atmosphere to obtain crystals. These crystals were then ball-milled using φ20 mm ZrO2 pebbles for 10 hours and passed through a resin sieve with a mesh size of 120 μm to obtain a coarse powder with an average particle size of 7 μm. Furthermore, this coarse powder was ball-milled using φ3 mm ZrO2 pebbles with ethanol as a grinding aid for 12 hours to obtain a crystalline powder with an average particle size of 0.2 μm. 70 wt.% of this crystalline powder was mixed with 30 wt.% polyethylene oxide nonylphenyl ether (mass-average molecular weight: 660), a nonionic surfactant, as a carbon source, and then dried at 100°C for 1 hour. Subsequently, firing was performed at 620°C for 30 minutes in a nitrogen atmosphere to obtain a positive electrode active material powder with an average particle size of 0.2 μm. Powder X-ray diffraction measurements of this positive electrode active material powder confirmed that the diffraction lines originated from Na2FeP2O7 crystals.

[0158] <Preparation of electrode composite material (active material layer)> The electrode mixture (active material layer) was prepared by filling a powder molding die (manufactured by NPA Systems Co., Ltd., Φ10 mm) with a polypropylene carbonate (PPC) coated mixture powder in an argon environment, applying a pressure of 30 MPa to form pellets, and then firing the pellets at 550°C for 1 hour at a rate of 3°C / min under a nitrogen (N2) / hydrogen (H2) mixed gas atmosphere (=96 / 4 vol.%). Subsequently, a 300 nm thick gold film was deposited on one side of the resulting pelletized electrode mixture as a current collector using physical vapor deposition (PVD). During the firing process, all the PPC contained in the electrode mixture was thermally decomposed and converted into carbon dioxide, so the weight of the resulting electrode mixture was the weight of the PPC minus the PPC.

[0159] The electrode mixture after firing had a thickness of 298 μm, a total weight of 0.0307 g, a diameter of 9.242 mm, and a weight of 0.02794 g of active material contained in the electrode mixture. SEM (scanning electron microscope) images of the cross-section of the electrode mixture revealed that it consisted of clusters formed by multiple linked positive electrode active material particles and had a porous structure including pores. These clusters were formed when the positive electrode active material precursor powder softened and flowed during the firing of the mixture powder, binding the positive electrode active material powders together. It was also confirmed that the positive electrode active material precursor powder crystallized as it softened and flowed, precipitating Na2FeP2O7 crystals.

[0160] The PPC-coated composite powder was obtained by adding N-methyl-2-pyrrolidone (NMP) to the cathode active material precursor powder, cathode active material powder, conductive additive, and PPC (32.3:48.5:2.5:16.7 wt%) in a dry environment (dew point below -40°C) using a self-rotating mixer (Sinky, Neritara, 2000 rpm, 1 h), then volatilizing and removing the NMP by heating and drying on a glass plate (80°C, 1 h), and finally grinding the mixture in a grinder (Nittokagaku, AMM-140D) (1 h). As the conductive additive, a mixture of carbon black and vapor-grown carbon fiber (Showa Denko, VGCF-H) in a ratio of 5:1 wt.% was used.

[0161] <Inorganic solid electrolyte> Composition formula Na 1.6 Li 0.34 Al 10.66 O 17 Li2O-stabilized β''-alumina (manufactured by Ionotec) was used as is. The thickness of the inorganic solid electrolyte was 1 mm.

[0162] <Preparation of organic solid electrolytes> The organic solid electrolyte was prepared by adding acetonitrile to polyethylene glycol (PEG) and NaPF6 (1:0.3 wt.) with a weight-average molecular weight (Mw) of 7000 and mixing them in a self-rotating mixer (Sinky, Neritara, 2000 rpm, 1 h).

[0163] <Fabrication of all-solid-state sodium batteries>

[0164] (Example 1: All-solid-state sodium battery) In Example 1, the battery was prepared in an argon environment, with an organic solid electrolyte of 0.005 g / cm³ between the electrode mixture and the inorganic solid electrolyte. 2 The electrode was fabricated by interposing the electrolyte in this manner and using sodium metal as the counter electrode. The organic solid electrolyte was interposed by applying an organic solid electrolyte dissolved in acetonitrile to the electrode mixture with a brush, and then vacuum drying (60°C, 1 hour).

[0165] (Example 2: All-solid-state sodium battery) The battery in Example 2 was prepared by adding a mixture of PEG and NaPF6 (1:0.3 wt.%) at a concentration of 0.006 g / cm³. 2 The battery configuration is the same as in Example 1, except that an electrode mixture was used that was filled in such a manner. The mixture to be filled into the electrode mixture was deacetonitrileized by immersing the electrode mixture in PEG and NaPF6 dissolved in acetonitrile, followed by vacuum drying (60°C, 1 hour).

[0166] (Example 3: All-solid-state sodium battery) The battery of Example 3 has the same battery configuration as in Example 1, except that a mixture of ethylene carbonate (EC) and NaPF6 (1:0.3 wt%) is filled into the electrode mixture. The mixture to be filled into the electrode mixture was prepared by immersing the electrode mixture in EC and NaPF6 dissolved in diethyl carbonate (DEC), followed by de-DEC treatment by vacuum drying (60°C, 1 hour).

[0167] (Example 1: All-solid-state sodium battery) The battery in Reference Example 1 has the same battery configuration as in Example 1, except that it does not have an organic solid electrolyte.

[0168] (Example 2: Liquid sodium-ion battery) The battery in Reference Example 2 does not have an organic or inorganic solid electrolyte, but instead uses a separator made by layering glass nonwoven fabric (Advantec, GA-100) and a polyolefin-based microporous membrane (Celgard, #2320), impregnated with 1M NaPF6 / (EC:DEC=1:1vol.), and otherwise has the same battery configuration as in Example 1.

[0169] <Battery Testing> Battery testing was performed by repeatedly charging and discharging at a constant current under the conditions of 60°C, a charge rate of 0.01C, and a cutoff voltage of 3.8 to 2.0V. The charge and discharge test results for Examples 1 to 3 and Reference Examples 1 and 2 are shown below.

[0170] (Example 1) In Example 1, the all-solid-state sodium battery integrated the electrode material and the inorganic solid electrolyte by interposing a mixture of PEG and NaPF6 as an organic solid electrolyte between the electrode material and the inorganic solid electrolyte. However, the battery had high resistance, and the discharge capacity of the active material was 10.1 mAh / g (0.42 mAh / cm²). 2 ) was.

[0171] (Example 2) In Example 2, the all-solid-state sodium battery had a mixture of PEG and NaPF6 as an organic solid electrolyte interposed between the electrode mixture and the inorganic solid electrolyte, thereby integrating the electrode mixture and the inorganic solid electrolyte. Furthermore, the organic solid electrolyte was impregnated into the electrode mixture. As a result, the discharge capacity of the active material was 89.2 mAh / g (3.72 mAh / cm²). 2 ) was.

[0172] (Example 3) In Example 3, the all-solid-state sodium battery had a mixture of PEG and NaPF6 as an organic solid electrolyte interposed between the electrode mixture and the inorganic solid electrolyte, thereby integrating the electrode mixture and the inorganic solid electrolyte. Furthermore, the organic solid electrolyte was impregnated into the electrode mixture. As a result, the discharge capacity of the active material was 92.6 mAh / g (3.86 mAh / cm²). 2 ) was.

[0173] (Reference example 1) The all-solid-state sodium battery in Reference Example 1 lacked an organic solid electrolyte, and therefore the electrode composite material and inorganic solid electrolyte were not integrated. Furthermore, the discharge capacity of the active material was 0.0 mAh / g (0 mAh / cm²). 2 ) meant that it did not function as a battery at all. This means that even when a tiny current of 0.01C was applied, there was significant resistance to ion flow at the interface between the electrodes and the solid electrolyte.

[0174] (Reference example 2) The liquid sodium-ion battery in Reference Example 2 has an active material discharge capacity of 94.2 mAh / g (3.92 mAh / cm²). 2 ) was.

[0175] <Battery overcharge test> The battery overcharge test was performed by constant current charging under the conditions of 60°C, 0.01C rate, and a charge cutoff voltage of 4.5V. Figure 9 shows a comparison of the charging curves for Example 3 and Reference Example 2. The vertical axis represents battery voltage, and the horizontal axis represents charging time. Charging exceeding 100 hours is considered the overcharge region.

[0176] As is clear from Figure 9, a charging plateau was observed around 4.2V in the battery of Example 3, and it did not reach the charging cutoff voltage of 4.5V. On the other hand, no charging plateau was observed around 4.2V in the battery of Reference Example 2, and it was charged up to the charging cutoff voltage. In the battery of Example 3, it is thought that the organic solid electrolyte interposed between the electrode mixture and the inorganic solid electrolyte underwent oxidative decomposition around 4.2V. From these results, it is shown that overcharging can be suppressed by incorporating an organic solid electrolyte in the battery.

[0177] Furthermore, when the battery of Example 3 was charged at a constant current and constant voltage until the State of Charge (SOC) reached 200% under conditions of 60°C, a rate of 0.01C, and a charge cutoff voltage of 4.5V, and then discharged at a constant current until the voltage reached 2.0V at a rate of 0.1C, it showed no discharge capacity. It is thought that the organic solid electrolyte underwent oxidative decomposition, increasing the battery resistance and causing it to shut down.

[0178] It should be noted that the method for manufacturing the electrode mixture used in the all-solid-state sodium battery of the present invention, and the method for manufacturing an all-solid-state sodium battery using the same, are not limited to the embodiments described above, and can be modified as appropriate without departing from the spirit of the present invention. [Industrial applicability]

[0179] As described above, the present invention provides a method for manufacturing an electrode mixture used in an all-solid-state sodium battery that can exhibit excellent charge-discharge cycle characteristics while maintaining a high discharge capacity at room temperature. The present invention also provides a method for manufacturing an all-solid-state sodium battery in which the electrode mixture obtained by the method is used as the negative electrode and / or positive electrode. These electrode mixtures and all-solid-state sodium batteries are expected to be applied to electric vehicles (EVs) and stationary power sources. [Explanation of Symbols]

[0180] 1… All-solid-state sodium battery 2...Electrode composite material 3...Organic solid electrolyte 4...Inorganic solid electrolyte 5…The opposite 6... Current collector 7…Cross-sectional concept of an active material cluster 8...Electrode active material particles 9…Crystals of transition metal oxides of polyphosphate 10…Conductive additive (carbon)

Claims

1. A method for producing an electrode mixture for use in an all-solid-state sodium storage battery, comprising: a step A of coating or supporting a resin-based binder on the surface of transition metal oxide polyphosphate particles to produce composite particles; A step B of filling a powder molding die with the composite particles and then applying pressure to obtain pellets; a step C of thermally decomposing the resin binder contained in the pellets by heat treatment to generate voids; A method for producing an electrode mixture comprising:

2. A method for producing an electrode mixture for use in an all-solid-state sodium storage battery, comprising: a step A of coating or supporting a resin-based binder on the surface of transition metal oxide polyphosphate particles to produce composite particles; A step B of filling a powder molding die with the composite particles and then applying pressure to obtain pellets; a step C of thermally decomposing the resin binder contained in the pellets by heat treatment to generate voids; and after step C, step D of immersing or coating the pellet in a liquid in which at least one selected from the group consisting of ethylene carbonate, polyethylene carbonate, polyethylene glycol, and polyethylene oxide is dissolved, thereby filling all or part of the voids.

3. 3. The method for producing an electrode mixture according to claim 1, wherein the step A is a step of producing the composite particles by drying a liquid in which the transition metal oxide polyphosphate and the resin-based binder are suspended in a solvent or a dispersion medium.

4. The method for producing an electrode mixture according to any one of claims 1 to 3, wherein the step A is a step of producing the composite particles by a spray drying method or a fluidized bed granulation method.

5. The method for producing an electrode mixture according to any one of claims 1 to 4, wherein the step B is a step of pelletizing by applying a pressure of 1 MPa to 100 MPa.

6. When the step C is carried out under an atmosphere of a mixed gas of at least an inert gas and hydrogen gas, and the volume of the entire mixed gas is 100 vol. %, The volume of the inert gas is within the range of 90 vol. % to 99.5 vol. %, The volume of the hydrogen gas is in the range of 0.5 vol. % to 10 vol. %, The method for producing an electrode mixture according to any one of claims 1 to 5, wherein the step comprises thermally decomposing the resin binder and simultaneously softening and fluidizing the transition metal oxide polyphosphate.

7. The step C is A temperature increase rate of 0.1°C / min to 50°C / min is maintained at a temperature of 400°C to 2000°C for 5 minutes to 10 hours, the resin binder is thermally decomposed, and simultaneously the transition metal oxide polyphosphate is softened and fluidized; The method for producing an electrode mixture according to any one of claims 1 to 6, which is a step of forming active material clusters in which a plurality of particles having particle sizes in the range of 0.1 µm to 100 µm are connected together.

8. The method for producing an electrode mixture according to any one of claims 1 to 7, wherein the resin-based binder is polypropylene carbonate.

9. The thickness of the electrode mixture is 10 μm to 5000 μm, The total weight per unit area of ​​the electrode mixture is 1 mg / cm 2 ~5000mg / cm 2 The method for producing an electrode mixture according to any one of claims 1 to 8,

10. A method for manufacturing an all-solid-state sodium storage battery in which an organic solid electrolyte is interposed between an electrode mixture and an inorganic solid electrolyte, a step A of suspending a transition metal oxide polyphosphate and a resin-based binder in a solvent or dispersion medium and drying the resulting suspension to coat or support the resin-based binder on the surfaces of transition metal oxide polyphosphate particles, thereby producing composite particles; A step B of filling a powder molding die with the composite particles and then applying pressure to obtain pellets; a step C of thermally decomposing the resin binder contained in the pellets by heat treatment; a step D, after the step C, of ​​immersing or coating the pellet in a liquid in which at least one selected from the group consisting of ethylene carbonate, polyethylene carbonate, polyethylene glycol, and polyethylene oxide is dissolved, thereby filling all or part of the voids; and a step E of applying the organic solid electrolyte to a surface of the electrode mixture or the inorganic solid electrolyte; and a battery assembly step F of laminating the electrode mixture and the inorganic solid electrolyte together.

11. The method for producing an all-solid-state sodium storage battery according to claim 10, wherein the organic solid electrolyte is polyethylene glycol or polyethylene oxide having a molecular weight of 1,000 or more and 1,000,000 or less.

12. 12. The method for producing an all-solid-state sodium storage battery according to claim 10 or 11, wherein the step E is a step of dissolving the organic solid electrolyte in a solvent to form a liquid, applying the liquid, and then drying the liquid.

13. The method for producing an all-solid-state sodium storage battery according to any one of claims 10 to 12, wherein the steps A to E are carried out in an environment with a dew-point temperature of minus 40°C or lower.

14. The method for producing an all-solid-state sodium storage battery according to any one of claims 10 to 13, wherein the inorganic solid electrolyte is an oxide-based solid electrolyte having a thickness of 1 mm or less and a porosity of 20% or less.

15. the inorganic solid electrolyte is aluminum oxide containing sodium, The method for producing an all-solid-state sodium storage battery according to any one of claims 10 to 14, wherein the carrier ions are sodium.